2021
DOI: 10.1186/s12889-020-10105-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination concerns, beliefs and practices among Ukrainian migrants in Poland: a qualitative study

Abstract: Background Ukrainians numbering approximately 1.2 million are the largest migrant group in Poland. Data on vaccination coverage among migrants are not collected in EU, including Poland. Therefore, this qualitative study aimed to identify vaccination practices in this migrant group, to explore facilitators and barriers to vaccination and related access to Polish healthcare services. Methods In September 2019, a qualitative study of Ukrainian migrant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…In a recent study of Venezuelan migrants in Latin America, 70% said they had access to a mobile phone, with the main communication channels being WhatsApp and Facebook, yet half said they felt uninformed 49 . We also found that some migrants and ethnic minorities used diaspora media as a source of COVID-19 related information during the pandemic, which merits further consideration in terms of understanding how to better engage these groups in preventative health care and vaccination, and has been previously reported in studies as influencing views and beliefs around vaccination 50 . Misinformation on social media correlated negatively with vaccine intention and our findings align with other research in this area and will undoubtedly be relevant to many other population groups 2 7 29 .…”
Section: Discussionsupporting
confidence: 59%
“…In a recent study of Venezuelan migrants in Latin America, 70% said they had access to a mobile phone, with the main communication channels being WhatsApp and Facebook, yet half said they felt uninformed 49 . We also found that some migrants and ethnic minorities used diaspora media as a source of COVID-19 related information during the pandemic, which merits further consideration in terms of understanding how to better engage these groups in preventative health care and vaccination, and has been previously reported in studies as influencing views and beliefs around vaccination 50 . Misinformation on social media correlated negatively with vaccine intention and our findings align with other research in this area and will undoubtedly be relevant to many other population groups 2 7 29 .…”
Section: Discussionsupporting
confidence: 59%
“…43 studies 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 addressed barriers to or facilitators of vaccine uptake. Access and acceptance were the most common themes, with awareness, affordability, and activation reported to a lesser extent.…”
Section: Resultsmentioning
confidence: 99%
“…
What are the barriers to and facilitators of vaccine uptake in migrants? Access Barriers Language, literacy, and communication barriers 26 , 28 , 36 , 37 , 38 , 39 , 43 , 44 , 46 , 53 , 55 , 58 , 59 , 60 , 64 , 65 , 67 Resource and capacity constraints 39 , 41 , 47 , 52 , 58 , 61 , 65 Practical barriers 34 , 39 , 41 , 42 , 44 , 45 , 47 , 59 Legal barriers 42 , 45 , 68 Distrust of health system or authorities; sense of alienation and disempowerment 8 , 34 , 39 , 58 , 59 , 60 Specific provider-level barriers 34 , 42 , 46 , 48 , 58 , 60 , 61 , 62 —eg, health professionals lacking specific knowledge of migrant entitlements or catch-up vaccination guidelines, missed opportunities to vaccinate Facilitators Social integration <...>
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is especially noticeable with regard to populations previously marginalized in pandemic social studies [24][25], i.e. the Polish elderly (disproportionately affected by the COVID-19), who need adequate support and information networks concerning the vaccination, as well as immigrants, who might be facing language barriers [29]. These groups are especially hardly able to properly estimate the risk-benefit ratio related to vaccination, so reaching them and providing information will be a key influencing factor.…”
Section: Methodsmentioning
confidence: 99%